The impact of dyslipidemia on prognosis of patients after endovascular abdominal aortic aneurysm repair - Luo, Xin; Guo, Qiang; Wang, Jiarong; Li, Yiyuan; Zhao, Jichun; Huang, Bin; Chen, Xiyang (Frontiers in Cardiovascular Medicine, 2024)
Introduction Dyslipidemia is common in patients with abdominal aortic aneurysm (AAA). However, there is insufficient research on the impact of dyslipidemia on the postoperative outcomes of patients with AAA after endovascular aortic aneurysm repair (EVAR). This study aimed to determine the impact of dyslipidemia on the prognosis of patients with AAA treated with EVAR. Method We retrospectively reviewed patients with AAA who underwent EVAR at our hospital between 2010 and 2020. The baseline characteristics and prognoses of patients in the dyslipidemia and non-dyslipidemia groups were analyzed. Results A total of 641 patients were included; the prevalence of dyslipidemia in patients with AAA was 42.3% (271/641), and the mean follow-up time was 63.37 ± 26.49 months. The prevalence of diabetes (10.0% vs. 15.1%, P = 0.050), peripheral arterial disease (17.3% vs. 25.8%, P = 0.018), and chronic kidney disease (3.0% vs. 6.3%, P = 0.043) was higher in the dyslipidemia group. The three-year all-cause mortality rate after EVAR was 9.98% (64/641), and there was no difference in the incidence of all-cause mortality (10.27% vs. 9.59%, P = 0.778) between the two groups. A total of 36 (5.62%) major adverse cardiovascular and cerebrovascular events (MACCEs) were observed within 3 years and were more common in patients with dyslipidemia (2.97% vs. 9.59%, P < 0.001). The incidence of stent-related complications in all patients was 19.97% (128/641), and there was no difference in the incidence of stent-related complications between the two groups (22.16% vs. 16.97%, P = 0.105); however, the incidence of type I endoleak in the dyslipidemia group was lower than that in the non-dyslipidemia group (9.19% vs. 4.06%, P = 0.012). Cox-regression analysis showed that high level of high-density lipoprotein cholesterol (HDL-C) was the protective factor (HR, 0.203, 95% CI, 0.067–0.616, P = 0.005) for MACCES, but it was the risk factor for type I endoleak (HR, 2.317, 95% CI, 1.202–4.466, P = 0.012). Conclusion Dyslipidemia did not affect the mortality of patients with AAA who underwent EVAR; however, it may increase the incidence of MACCEs. Dyslipidemia may decrease the incidence of type I endoleaks after EVAR; however, further studies are warranted. We should strengthen the postoperative management of patients with dyslipidemia, prevent the occurrence of MACCEs.